PENDIDIKAN MORAL PERSPEKTIF ISLAM DI ERA POST-MODERN - Nakhma’ussolikhah, Nakhma’ussolikhah (Lembaga Penelitian Dan Pengabdian Masyarakat Stai Brebes, 2025)
The development of the post-modern era has brought significant changes to human value systems and thought patterns, including aspects of morality. The relativism, individualism and secularization that are the main characteristics of post-modernity often blur the lines between right and wrong, good and bad. In this context, Islamic perspective moral education has a strategic role as a spiritual and ethical foundation in building civilized human character. The aim of this research is to examine the concept of Islamic moral education and its relevance in facing moral challenges in the post-modern era. A descriptive qualitative approach is used through literature studies that examine classical and contemporary works of Muslim scholars and thinkers. The results of the study show that moral education in Islam not only emphasizes the cognitive and affective dimensions, but also the spiritual dimension which is rooted in the values ​​of monotheism, morals, and the balance between rationality and spirituality. Values.